Composite inorganic separator for lithium batteries with three-dimensional electrodes

By using composite inorganic separators composed of interwoven non-conductive inorganic fibers and inorganic particles, the problems of insufficient thickness and complex production in lithium batteries are solved, and the separators with high absorption and high porosity are realized, which improves the safety and performance of the battery.

CN119604993APending Publication Date: 2025-03-11HE3DA SRO
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202380055365.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-05
Filing Date
2023-07-04
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

In the existing lithium battery cells, the thickness of the partition is not enough to prevent the growth of lithium metal dendrites, resulting in battery safety and reliability problems. At the same time, the production process is complex, the weight is high, and the porosity is not easy to adjust.

Method used

Using a composite inorganic partition formed of interwoven non-conductive inorganic fibers, the fiber length and thickness are within a specific range, and the porosity is adjusted by blending the inorganic particles to form a high absorbency and high porosity separator.

Benefits of technology

It realizes easy preparation, high strength, low specific resistance and high mobility of the separator, effectively prevents the growth of lithium metal dendrites, improves the safety and reliability of the battery, and improves the charging and discharge rates.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005251905360000011
    Figure HDA0005251905360000011
  • Figure HDA0005251905360000012
    Figure HDA0005251905360000012
  • Figure HDA0005251905360000021
    Figure HDA0005251905360000021
Patent Text Reader

Abstract

The present invention provides a separator for a lithium battery having an electrode having a thickness greater than 0.1 mm, characterized in that the separator is formed from interwoven non-conductive inorganic fibers, optionally with a blend of non-conductive inorganic particles; wherein the length of the fiber is in the range of 0.5 mm to 30 mm, and the thickness of the fiber is in the range of 20 nm to 1500 nm; wherein the fiber is made of glass; the aperture of the separator is in the range of 0.02 [mu] m to 2.5 [mu] m, where the aperture of the separator is an average aperture of the separator determined by averaging at least 50 pore diameter values read from an electron microscope image; the absorbency of the separator, expressed as the weight of the electrolyte 1MLiPF6 soaked in ethylene carbonate / dimethyl carbonate at a volume ratio (v: v) of 1: 1, is 1 to 10 times the weight of the separator.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an inorganic composite separator with adjustable pore size for use in rechargeable, especially high-rate, lithium battery cells with spatially arranged three-dimensional (3D) electrodes. Background Art

[0002] Most rechargeable lithium battery cells produced today are based on very thin sheet electrodes made of a mixture of active material, conductive carbon and an organic binder, which are laminated in thin layers onto a foil of conductive material, usually aluminum or copper (current collector). The thickness of these planar electrodes is usually about 50 microns (rarely more than 100 microns). The positive and negative electrodes are stacked on top of each other, separated by a thin intermediate layer of porous, non-conductive material (separator), which is usually a perforated foil made of an organic polymer and / or a combination of polymers and inorganic oxides. The stacked electrodes separated by the separator are then compressed, closed, and the spaces are filled with an electrolyte. A non-aqueous solution of a lithium salt is used as the electrolyte.

[0003] During the charge and discharge process of these planar electrodes, it is extremely important to prevent the formation of lithium metal dendrites, which are formed, for example, during excessively fast charging or discharging. Lithium metal is deposited on the electrodes in the form of dendrites, which grow through the separator and can cause an electrical short between the two electrodes. The short circuit heats up, and the increased temperature causes the organic polymer separator to shrink. This makes the short circuit more robust and often leads to thermal runaway of the battery cell.

[0004] Manufacturers try to add inorganic substances to the composition of the separator to reduce the shrinkage coefficient. The composite separator must be as thin as possible to maintain a high specific capacity of the battery. The typical thickness of the current separator is below 15 microns, often even below 10 microns, while the dendrites sometimes grow to hundreds of microns, usually 50 microns. Therefore, for this reason, it is practically unthinkable to use metallic lithium for the negative electrode of a thin-film planar arrangement when the thickness of the separator is much smaller than the length of the lithium dendrite.

[0005] Commonly used organic polymers shrink at temperatures above 50° C. Therefore, in order to reduce the shrinkage of the separator, a composite separator is used, which includes a combination of a polymer and an inorganic material that does not shrink at elevated temperatures.

[0006] Known composite separators are made of:

[0007] 1) Organic polymers and inorganic fillers, or

[0008] 2) at least one layer of an inorganic binder fully or partially covered with an organic polymer, or

[0009] 3) Inorganic materials with particles of varying roughness, which are connected during the preparation process by an organic binder which is subsequently cured or fired.

[0010] US6432586 and EP1146576 describe a ceramic separator for a 2D (planar thin film) electrode coated by lamination of a polymer microporous layer. The ceramic layer is composed of 20% to 95% Al-based 2 O 3 or SiO 2 、CaCO 3 or TiO 2 The invention relates to a non-conductive particle having a particle size of 0.001 micron to 25 microns, which is distributed in a conductive polymer matrix (which can be an electrolyte). This thin ceramic layer of 0.001 micron to 50 microns thick prevents lithium dendrites from growing through. An additional polymer layer of 5 microns to 50 microns thick is provided to prevent ions from flowing between the positive and negative electrodes in the event of a thermal failure.

[0011] The choice of inorganic materials for plastic separators is very limited. These materials must be non-conductive, must not intercalate lithium, must have a stable oxidation state, must withstand hydrofluoric acid and chemical environments, and must have a very small particle size.

[0012] As shown in a study quantifying the effect of separator thickness on the rate performance of lithium-ion batteries (Dominik V. Horváth et al., 2022 J. Electrochem. Soc. 169 030503), using thicker plastic separator layers (up to 16 μm to 100 μm) greatly reduces the charge and discharge rates and capacity utilization. The authors point out that the main source of the problem is the high resistance of the electrolyte in the separator, rather than the diffusion of ions through the separator.

[0013] US2005 / 221192 describes a method based on Al 2 O 3 or Zr 2 O 3 and SiO 2 A thin film ceramic separator having a porosity of 30% to 70%. The separator comprises at least two particle size fractions differing by at least 10 microns. The larger particle is Al 2 O 3 or Zr 2 O 3 , the smaller particles are Zr 2 O 3 and SiO 2The preferred thickness of the separator layer is 10 microns to 15 microns. Preferably, the separator comprises a silicone adhesive for better cohesion and bonding to the electrode. When a very thin separator layer is formed in situ on the electrode, the separator is applied to the electrode as a suspension at a higher temperature.

[0014] EP1803177, US2008032197 and WO2006045339 describe inorganic separators for thin-film lithium batteries, methods for their production and their uses. The separator-electrode unit comprises an inorganic separator layer and an electrode, wherein the inorganic separator layer comprises at least two metal oxide particle portions, which differ from each other in average particle size and / or different metal oxides, and whose active mass particles are bonded to the working electrode by an inorganic binder. In this way, separator thicknesses of less than 15 microns can be achieved. The disadvantage is that a separator comprising only powdered ceramic material has a separator weight that is too high (in g / m2) even with a relatively thin separator layer. 2 count).

[0015] As an example of a current thick layer separator, WO 2019195605 can be mentioned. It describes a composite separator for primary batteries (non-rechargeable) comprising a layer of glass fibers, a layer of polymer and possibly a binder. The thickness of the separator layer used in Al-graphite batteries is 60 to 200 microns. There can be several layers, in which a glass fiber layer is combined with a polymer layer. The glass fiber layer or the polymer layer can contain a layer made of glass fibers (also for example SiO 2 The invention relates to a method for preparing a lithium-ion battery comprising a cellophane made of lithium ion (Li-O-G) fiber. The cellophane is porous, with pore sizes ranging from 0.1 microns to 10 microns. The glass fiber paper (GFP) is highly porous, so a thick separator is required for use, in which an excess of electrolyte is required. Therefore, such a strong separator containing only GFP and electrolyte is not commercially viable, so it is combined with a polymer layer. The negative electrode is Al. The application mentions that the negative electrode can also be metallic Li. The positive electrode contains graphite. However, the electrochemical potential difference between lithium and graphite is only 0.2V, so the practical utilization of Li-graphite batteries is actually minimal.

[0016] Similarly, glass fiber separators designed for lead-acid batteries are not suitable for lithium batteries because their pore size is designed to retain the mechanically debonded portion of the electrodes and is many times larger (about 30 microns) than is needed to separate the lithium electrodes and prevent lithium metal dendrite growth.

[0017] WO2019070945 describes a separator for a Li-S battery, the separator comprising a material capable of absorbing and desorbing polysulfides. The composition of the separator ensures that the sulfur loss from the positive electrode during the cycle is reduced, thereby improving the cycle life. The lithium-sulfur battery comprises a lithium metal negative electrode and a sulfur-containing positive electrode, with a space between them, and a multifunctional separator is located in the space. The separator comprises an active material capable of absorbing and desorbing polysulfides, and the electrolyte is in contact with the active material. The active material of the separator comprises a metal nitride or a metal oxynitride, wherein the porosity of the metal nitride or the metal oxynitride is 20% or more. The separator comprises a porous support in the form of a microporous sphere, the porous support being formed by mesoporous nanoparticles, porous hollow carbon, graphene oxide layers, porous carbon nanofibers, hollow carbon fibers, metal foams, metal networks, or a combination thereof, and optionally the porous material comprises carbon, graphene, graphene oxide, metals, and a combination thereof, or a polymer coated with an active material. Nitride or oxynitride compounds may also be used as a separator core, the core being coated with a coating containing a metal nitride or oxynitride, the coating having a different composition than the core.

[0018] WO2010031363 solves the problem and formation of dendrites in thick layer (3D) electrodes. At least one electrode contains an active material having a hollow sphere morphology (the wall thickness of the hollow sphere is up to 10 microns), and / or contains an active material in the form of aggregates and / or agglomerates with a size of 30 microns, and the active material is capable of absorbing and releasing lithium in the presence of an electrolyte. This material allows the formation of thick electrodes by pressing, without the need for organic binders, with a minimum thickness of 0.5 mm, a high active material content, and a porosity of 25% to 90% for the pressed electrode. Three-dimensional electrodes allow the formation of thick separators with a thickness of 0.1 mm to 10 mm, which contain highly porous non-conductive ceramic materials with open pores and a porosity of 30% to 95%. The separator is made of Al-based 2 O 3 or ZrO 2 The separator has a non-oriented morphology of the pyrolysis product or the non-woven glass or ceramic fibers. The advantage of such a separator is that its thickness prevents dendrites from growing through it. However, the biggest disadvantage is that the dry powder must be mechanically pressed into the final shape during production, which brings problems of mechanical damage to the electrode and uniformity of the compressed layer in the case of larger areas. These powder separators consist of particles that do not have self-supporting properties and must be produced in situ by compression. Here, the final porosity of the separator can only be adjusted by the final compression. The particle weight is also quite high, especially when using a specific gravity of 5.68 g / cm 3 ZrO 2 under the circumstances.

[0019] EP2727171 describes a Li battery with a three-dimensional electrode as described in EP 2371019 and US10581083, wherein a Li battery containing a three-dimensional electrode based on Al is used. 2 O 3 、SiO 2 、ZrO 2 , glass, compressed inorganic ceramic materials in the form of nanofibers, fibers or organic porous foils. Also in this case, inorganic separators have the same problems related to the lack of tunability of pore size, the structural capacity of the separator, and the processing problems of the separator.

[0020] As is evident from the cited literature, known rechargeable lithium battery cells are mostly produced on the basis of thin film planar electrodes. The thickness of these planar electrodes is usually about 50 microns (rarely more than 100 microns). Instead of polymer separators, composite separators comprising various polymers or mixtures thereof with ceramic materials, or combinations of ceramic material layers and polymer layers are used or applied to the electrodes. The preparation of these separators is rather complicated and usually requires the use of various adhesives and subsequent heat treatment to remove these adhesives.

[0021] A battery using a separator comprising only inorganic material powder has the disadvantage of being high in weight.

[0022] The disadvantages of using cellophane for lithium batteries are its thickness and large pores.

[0023] Today, the thicknesses of electrodes and separators are precisely calculated and proportioned, and the transport of lithium ions and the formation of metallic lithium dendrites (= lithium metal dendrites) are also optimized by engineers. Any variation in the ratio of their thicknesses or other parameters such as capacity means a degradation in the safety, reliability and performance of the battery. Lithium dendrites are mainly formed during the charging of the battery cells and grow to a size of more than 50 micrometers. The formation of lithium dendrites depends strongly on the uniformity of the separator. Lithium dendrites usually form in the weakest part of the separator. The thinner the separator, the more difficult it is to ensure its uniformity. The temperature also has a fundamental influence on the formation of dendrites, with extremely high demands being placed on the quality of the separator at temperatures below freezing, below which the charging rate must be radically reduced, especially when graphite is used as the negative electrode.

[0024] Thicker electrodes, higher capacities, and lithium contents place more demands on separators.

[0025] The prior art shows that typical disadvantages of known separators for lithium accumulators with thick-layer electrodes include the laborious production of layered composite materials, the use of inorganic particles in combination with organic polymers and binders, a high weight related to their layer thickness, the disadvantage of large pores when using cellophane as separator or as part of a composite separator combined with an organic polymer, or pressing and handling problems for pure powder ceramic separators. Summary of the invention

[0026] The disadvantages listed above of separators for lithium batteries with three-dimensional (thick layer) electrodes with a thickness of at least 0.1 mm, such as the laborious production of layered composites, the use of a combination of inorganic particles with organic polymers and binders, the high weight related to their layer thickness, the disadvantage of large pores when using cellophane as a separator or as part of a composite separator combined with an organic polymer, or the pressing and handling problems of ceramic powder separators, are solved by composite inorganic separators for lithium batteries with three-dimensional (thick layer) electrodes.

[0027] The separator for lithium batteries according to the present invention is formed by interwoven non-conductive inorganic fibers (optionally together with an admixture of non-conductive inorganic particles); wherein the length of the fibers ranges from 0.5 mm to 30 mm, and the thickness of the fibers ranges from 20 nm to 1500 nm; wherein the fiber material is glass. The pore size of the separator is in the range of 0.02 microns to 2.5 microns, preferably in the range of 0.02 microns to 1 micron, wherein the pore size of the separator is defined as the average pore size of the separator determined by averaging at least 50 pore diameter values ​​measured from an electron microscope image. The absorption capacity (absorbency) of the separator is expressed as EC / DMC (ethylene carbonate / dimethyl carbonate; volume ratio (v:v) = 1:1; specific gravity at 25°C is 1.3 g / cm 3 ) in 1M LiPF 6 The absorbency (absorbency) of the separator by weight of the soaked electrolyte is 1 to 10 times the weight of the separator (i.e., 100% to 1000% absorbency), preferably 4 to 10 times the weight of the separator (i.e., 400% to 1000% absorbency).

[0028] The porosity of the separator is preferably higher than 20%, preferably higher than 50% (determined by calculation as the ratio of the volume of the separator to the volume of the soaked electrolyte, the volume of the soaked electrolyte being 1M LiPF in EC / DMC). 6 The weight ratio of the separator before and after electrolyte immersion was calculated).

[0029] The porosity of the uncompressed separator is preferably in the range of 50% to 90%. More preferably, the porosity of the uncompressed separator is higher than 80%, most preferably in the range of 75% to 90%.

[0030] The porosity of the separator after compression with a force of 100 kPa is preferably in the range of 20% to 55%.

[0031] Preferably, at least 90% by weight of the inorganic fibers have a thickness in the range of 20 nm to 500 nm.

[0032] The pore size of the separator is preferably in the range of 0.02 microns to 2.5 microns, more preferably 0.02 microns to 1 micron (i.e., 20 nm to 1000 nm), even more preferably in the range of 20 nm to 500 nm. In some embodiments, the pore size of the separator is in the range of 20 nm to 150 nm (especially if the separator contains inorganic particles).

[0033] Glass is a material based on silicon dioxide, which may also contain a mixture of at least one oxide of an element from group IA, IIA or IIIA of the periodic table. Preferably, the glass is selected from a material based on aluminoborosilicates or aluminosilicates with alkaline oxides such as CaO, MgO or B 2 O 3 ) of the admixture group A, C, D, E, R. For example, the glass can be silicate glass, potassium lime glass, soda lime glass, borosilicate glass.

[0034] In the case where non-conductive inorganic particles are present, the mass (weight) fraction of the particles is at most 20 wt % relative to the total weight of the separator.

[0035] The non-conductive inorganic particles may be particles with a maximum dimension of 10 nm to 700 nm, preferably up to 500 nm, more preferably with a maximum dimension in the range of 200 nm to 300 nm. Such particles may be formed from non-conductive metal oxides. In a preferred embodiment, these metal oxides may be, for example, silicon dioxide, aluminum oxide, or titanium dioxide.

[0036] The non-conductive inorganic particles may also be glass fibers having a length of at most 20 micrometers, preferably at most 10 micrometers, and a thickness in the range of 20 nm to 1500 nm.

[0037] The fibers form a macroporous matrix, wherein the non-conductive inorganic particles are mechanically attached to the fibers and in the structure of the macroporous matrix without the use of any binder. If the inorganic particles completely fill the pores of the matrix, they form a crust with a pore size smaller than the size of the inorganic particles. In this way, the pore size of the separator can be adjusted and optimized.

[0038] The separator does not contain any organic binder. The separator also does not contain any inorganic binder. Inorganic binders are powdery substances that can be used to bind fibers after contact with liquid (water).

[0039] The separator according to the present invention is made of inorganic substances only, resulting in at most three types of porosity, which constitute the final porosity of the separator. The three types of porosity are - the porosity of the matrix, the porosity of the partially reinforced matrix fibers, and the porosity of the fully filled matrix.

[0040] The inorganic material forming the inorganic particles according to the present invention is a ceramic material and / or glass, the ceramic material is selected from the group consisting of silicon oxide, aluminum oxide, zirconium oxide, titanium oxide, silicate, titanate, aluminosilicate, zirconium silicate, basalt and / or a mixture thereof, the glass is selected from the group consisting of aluminoborosilicate or aluminosilicate and alkaline oxides (such as CaO, MgO or B 2 O 3 ) of groups A, C, D, E, and R of admixtures.

[0041] The thickness of the separator after being compressed with a force of 100 kPa preferably ranges from 0.050 mm to 2 mm.

[0042] The area density of the separator layer is preferably in the range of 10 g / m 2 Up to 200g / m 2 .

[0043] In a preferred embodiment, the 2 Up to 200g / m 2 The separator having an area density of 20% to 95% has a porosity of at least 50% in the absence of compression, and even more preferably 75% to 90% in the absence of compression; and has a pore size of 50nm to 1500nm, preferably less than 500nm, and most preferably at most 150nm.

[0044] In separators for Li-S cells, the separator matrix may also be filled with particles that prevent polysulfide migration, such as titanium dioxide, titanium nitride, graphene, zirconium dioxide.

[0045] The separator according to the invention is prepared by the following process: firstly, the glass fibers are dispersed in water, the acidity of the mixture is adjusted to a pH value in the range of 2 to 5 (preferably 2.5 to 4), the mixture is then poured through a sieve, and the resulting layer is dried at a temperature of 100° C. to 200° C., resulting in the formation of a macroporous matrix. If the separator will also contain inorganic particles, these particles are introduced into the macroporous matrix in the form of a suspension or dispersion in water. Subsequently, the macroporous matrix without or with inorganic particles is fired at a temperature of 300° C. to 800° C.

[0046] Another aspect of the invention is a lithium battery containing at least one pair of electrodes separated by a separator according to the invention, wherein the thickness of the (compressed) separator is selected so that its ratio to the thickness of the electrodes is 1:2 to 1: 10. The electrodes preferably have a thickness of 100 micrometers to 4 millimeters, more preferably 0.3 mm to 2 mm, most preferably 0.5 mm to 1 mm.

[0047] Lithium battery electrode materials are well known to those skilled in the art.

[0048] An advantage of the separator according to the invention is that it is easy to manufacture. An aqueous suspension of inorganic nanofibers is poured through a sieve and dried. A mesoporous matrix is ​​obtained with a pore size of typically 20 nm to 2500 nm. This matrix can be used as a separator for low power batteries or it can be modified to a form suitable for high power batteries by pouring an aqueous suspension of non-conductive inorganic particles through the matrix, drying / firing again and cutting into separators.

[0049] Therefore, the matrix is ​​supplemented with inert, non-conductive inorganic material particles with a size of 10 nanometers to 700 nanometers, which are attached to the fibers and / or to the mesoporous structure of the matrix by van der Waals forces without the use of any adhesive. In areas where the pores completely fill the matrix, the inorganic material particles form a shell layer with a pore size smaller than the corresponding size of the inorganic material particles applied. These inorganic materials can preferably be ceramic materials, glass, basalt and insoluble metal oxides. The structural modification of the matrix ensures low specific resistance and high mobility of lithium ions when passing through the separator (even at a thickness of several millimeters). In addition, the structural modification of the matrix prevents the growth of lithium metal dendrites, improves the safety and reliability of the separator, and allows to increase the charging rate and discharge rate of the accumulator.

[0050] Due to van der Waals forces and the absence of chemical binders, the resulting separator has high strength, flexibility and chemical resistance.

[0051] In this way, layers with different densities and pore sizes can be formed in the separator. Porosities with pores smaller than in the original fiber matrix of up to 70% can be formed in the voids of the matrix fibers. In the areas where the pores of the matrix are completely filled with inorganic material particles, especially at the surface of the matrix, the particles form a shell layer with a defined pore size smaller than the corresponding size of the applied inorganic material particles. Inside the matrix, depending on the characteristics of the applied inorganic material particles, these particles adhere to the fibers of the matrix to a greater or lesser extent, forming a mesoporous layer with controlled pore size and density.

[0052] Modification of the matrix improves the reliability of the separator in terms of electrical separation of the electrodes, ionic conductivity, and prevention of dendrite growth through the separator.

[0053] Depending on the inorganic material used, the separator can easily withstand high temperatures even in the range of 500°C to 1000°C, and the separator has high pressure drop, excellent ion conductivity, zero conductivity, and therefore has excellent separation performance.

[0054] Due to the wettable surface and completely open pores of the inorganic material, the separator has a high mobility of lithium ions in the separator structure, which enables safe charging of the energy storage device even at high rates.

[0055] Even at higher battery charging rates, the separator according to the invention has excellent resistance to the growth of metallic lithium dendrites (= lithium metal dendrites). Thicknesses of 50 to 1000 microns, small pore sizes and very good uniformity are associated with higher battery safety.

[0056] The separator can also be used in Li-S battery cells, acting as an ion membrane, preventing the migration of polysulfides formed on the positive electrode and destroying lithium when the molecules of the polysulfides come into contact with lithium metal. In this case, the matrix additionally comprises particles that prevent the migration of polysulfides, which are selected from the group consisting of metal nitrides or metal nitride oxides, graphene and / or graphene oxide, attached to the nanofibers and attached to the inside of the mesoporous structure together with particles of non-conductive glass or ceramic material with a size of 10 nm to 700 nm.

[0057] The separator has chemical resistance to a fluorine-containing nonaqueous electrolyte.

[0058] The thickness of the separator is preferably in the range of 50 microns to 1000 microns, the porosity is 20% to 95%, the pore size is 20nm to 2500nm, preferably 70nm to 150nm. The area density of the separator is preferably 20g / m 2 Up to 500g / m 2 (weight per unit area).

[0059] The pressure loss of the separator is at least 300Pa / 100g / m 2 , preferably more than 1000Pa / 100g / m 2 .

[0060] Another advantage is the high absorbency and strength of the separator, with a high specific strength of 0.3 km to 2.0 km and a compressibility of up to 70% without any damage. BRIEF DESCRIPTION OF THE DRAWINGS

[0061] Figure 1 is a SEM image of the upper side of the separator of Example 1, with a size scale bar.

[0062] Figure 2The voltage curve of the battery cell of Example 1 is shown, which is charged for 8 hours and discharged for 8 hours.

[0063] Figure 3 The glass-Al of Example 2 is shown. 2 O 3 Electron microscope image of the structure (wrapped fibers, and partially filled pores) of the composite inorganic separator.

[0064] Figure 4 The glass-Al of Example 3 is shown. 2 O 3 The structure of the composite inorganic separator (wrapped fibers, filled pores, and dense and uniform Al2O3 formed on the matrix surface) 2 O 3 Electron microscope image of the shell.

[0065] Figure 5 The voltage curves of the battery cell of Example 3 at a 1.5-hour charge rate and a 1.5-hour discharge rate are shown.

[0066] Figure 6 The glass-TiO of Example 4 2 Electron microscope cross-sectional image of the composite separator.

[0067] Figure 7 The oriented matrix nanofiber structure with a thickness of 446 nm is shown to be filled with TiO 2 Nanoparticles, the TiO 2 Cross-section of a separator (Example 5) in which the nanoparticles have penetrated to a depth of about 200 microns, forming pores of about 25 nm in diameter, as provided by electron microscopy.

[0068] Figure 8 To show that there is TiO on the surface 2 Electron microscope image of the separator matrix of the nano-anatase shell (Example 5).

[0069] Fig. 9 A cycle diagram of the battery cell of Example 5 is shown.

[0070] Fig.10 A cycle diagram of the battery cell of Example 6 is shown.

[0071] Fig.11 A cycle diagram of the battery cell of Example 7 (comparative example) is shown.

[0072] Fig.12 A cycle diagram of the battery cell of Example 8 (comparative example) is shown. DETAILED DESCRIPTION

[0073] Example

[0074] method:

[0075] The composition of the separator (weight % of fibers and weight % of inorganic material) was determined gravimetrically by weighing the components (ie, matrix and inorganic material) using a precise laboratory balance. The inorganic material particles were captured by the matrix with less than 5% weight deviation (loss).

[0076] Separator thickness: Without any external pressure and at a constant pressure of 20 kPa, in VEB Measured on a FREIBERG thickness gauge with a contact area of ​​10 cm 2 . The values ​​are expressed in mm.

[0077] The separator thickness measurement after compressing the separator with a force of 100 kPa was performed on a LWBK thickness gauge (AB Lorentzen & Wettre), type 1-2, with a constant contact pressure of 100 kPa, a contact surface diameter of 16 mm, and a contact surface size of 2 cm 2 . The values ​​are expressed in mm.

[0078] A 100 mm x 100 mm sample was removed from the separator and the area density was measured gravimetrically by weighing the sample to the nearest 0.01 g and normalizing the weight to 1 m 2 Area density is expressed in g / m 2 Given as units.

[0079] The absorption (electrolyte soaking) was determined gravimetrically as the electrolyte (EC / DMC (ethylene carbonate / dimethyl carbonate; volume ratio (v:v) = 1:1; specific gravity at 25°C: 1.3 g / cm 3 ) in 1M LiPF 6 ) refers to the weight of the separator before immersion. The electrolyte immersion is performed until the weight of the immersed separator is constant. The weight of the immersed electrolyte is calculated as the difference between the weight of the separator after immersion and the weight of the dry separator (before immersion). The absorbency is measured with an uncompressed separator.

[0080] The porosity was determined by calculation based on the volume (area x thickness) and the electrolyte volume, which was calculated from the difference in weight of the separator before and after electrolyte soaking.

[0081] Porosity [%] = separator volume / electrolyte volume

[0082] Porosity determination method used:

[0083] 1) No compression - a 10 cm x 10 cm separator with a thickness determined by a thickness gauge was weighed and then weighed with a given specific density of 1.3 g / cm 3 The separator was immersed in electrolyte and weighed again. In this way, the volume of the electrolyte was determined and the porosity was calculated according to the above formula, where the volume of the separator was calculated as the product of 10 cm x 10 cm x the thickness determined by the thickness gauge.

[0084] 2) Compression at 100 kPa - 40 separators of 10 cm x 10 cm were weighed and stacked on top of each other between plane parallel metal plates and compressed with a force of 100 kPa. The weight and thickness (distance between plates) of this stack were measured to determine the volume of the separator. When the electrolyte was immersed in the compressed separator stack, the compressed separator stack was immersed in the electrolyte for 4 hours. Subsequently, the weight increase after electrolyte immersion was determined and the volume of the electrolyte was calculated by dividing by the specific density of the electrolyte. The porosity of the compressed separator was further calculated according to the formula given above.

[0085] Using electron microscopy, pore size was determined by reading the dimensions of at least 50 pores from the image and calculating the average of these dimensions.

[0086] The pressure loss is The measurement was carried out on a micromanometer of the UMK type with a tiltable arm at the setting conditions of the rotor flowmeter 75 (5 l / min; 0.0167 m / s). The function was checked using a so-called calibration plate with a calibration value of 300 to 310. The values ​​are given in Pa / 100 g / m 2 It is expressed as a unit.

[0087] Strength was measured on a Labor Tech break machine Labtest 2.005S. IEC 60050-212, values ​​are expressed as specific strength in km.

[0088] Electrochemical measurement methods were performed on a BaSyTec battery test system. The methods used included potentiometry, amperometry and voltammetry.

[0089] Embodiment 1:

[0090] The inorganic silicon dioxide (SiO 2) fibers were dispersed in water, the mixture was diluted and the acidity was adjusted to pH 4. The mixture was then distributed through a sieve, forming a regular layer on the sieve, which was dried at a temperature of 250° C. and subsequently fired at a temperature of 700° C. to form a porous separator matrix. The matrix prepared in this way was cut into the desired separator shape, which was used in a battery with 1 mm thick electrodes. The separators showed the following properties:

[0091] Thickness of separator without compression - 0.3mm

[0092] Thickness of separator after compression with 100 kPa - 0.15 mm

[0093] Area density - 50g / m 2

[0094] The electrolyte absorption is 1:6.2 based on the weight of the uncompressed separator.

[0095] The porosity before compression is 79%, and the porosity after compression with a force of 100 kPa is 40%

[0096] Pore ​​size < 500 nm as determined by electron microscopy

[0097] Separator pressure loss -720Pa / 100g / m 2 .

[0098] Figure 1 A photograph taken using a field emission electron microscope (FE SEM) is shown of the upper side of the separator of Example 1. As can be seen from the image, the typical pore size is about 500 nm (0.5 μm).

[0099] The separator was used to construct a 1 mm electrode thickness (3D), a lithium nickel manganese cobalt oxide (NMC-LiNi x Co (1-x) / 2 Mn (1-x) / 2 O 2 ) as the positive electrode and graphite as the negative electrode, the test battery cell has excellent discharge performance (up to 1000A peak and 50A continuous value), showing full capacity utilization (500Wh), low specific resistance and low Coulombic loss (<5%).

[0100] It can be fully charged from the discharged state at a rate of C / 4 (4 hours). A typical constant current charge-discharge voltage curve under relatively slow cycles of 8 hours of charge and 8 hours of discharge was measured by a commercial BaSyTec battery test system and is shown in Figure 2 middle.

[0101] Embodiment 2:

[0102] Inorganic glass fibers, typically 0.5 to 5 mm in length and 20 to 1500 nm in thickness, are dispersed in water, the mixture is diluted and its acidity adjusted to a pH of 2.5. The mixture is then poured through a moving fine sieve, where it forms a uniform layer, which is then dried at 150° C. to form a porous matrix. Alumina ceramic particles having an average particle size of 250 nm are introduced into the matrix by a wet process. The ceramic particles penetrate into the interior of the matrix and cover the fibers of the matrix. The composite material is dried at 350° C. to form a layer of separator matrix, from which separators of the desired shape are then cut and used in a battery having a three-dimensional electrode with a thickness of 0.5 mm.

[0103] These separators show the following properties:

[0104] Composition: Glass (90%), Al 2 O 3 (10%)

[0105] Thickness without compression - 0.32mm

[0106] Thickness after compression with 100kPa force - 0.17mm

[0107] Area density of separator - 45g / m 2

[0108] The electrolyte absorption was 590 wt % based on the weight of the uncompressed separator.

[0109] The porosity before compression is 64%, and the porosity after compression with a force of 100 kPa is 34%

[0110] Pore ​​size <300nm

[0111] Pressure drop - 950Pa / 100g / m 2 .

[0112] Figure 3 An image of the upper side of the separator taken using a field emission electron microscope (FE SEM) is shown.

[0113] The NMC / graphite chemistry-based battery cells with 1 mm electrode thickness (3D) built using this separator have excellent discharge performance (up to 1000 A), full capacity utilization (500 Wh), and low losses (<4%).

[0114] Charging from a discharged state can be done safely at a rate of C / 3 (3 hours). When the cell was overcharged at three times the recommended current, lithium separator penetration occurred at a voltage of 4.17V.

[0115] Embodiment 3:

[0116] Inorganic potassium calcium glass fibers, typically 0.5 mm to 5 mm in length and 20 nm to 1500 nm in thickness, are dispersed in water, the mixture is diluted and the acidity is adjusted to pH 3. The mixture is then poured onto a moving sieve, where it forms a uniform layer, which is dried at 150°C to form a porous matrix. Alumina ceramic particles having an average particle size of 250 nm are introduced into the matrix by a wet method. The ceramic particles penetrate into the interior of the matrix, mechanically adhere to the fibers of the matrix, fill the pores of the matrix, and form a dense and uniform Al2O3 layer on the surface. 2 O 3 Shell. In this way, the pore size of the composite material becomes 150nm on average ( Figure 4 ). The composite material was subsequently dried at 350° C. to form a layer, from which separators were cut and used in a battery cell having a 0.5 mm thick three-dimensional electrode.

[0117] The separators show the following properties:

[0118] Composition: Glass (88%), Al 2 O 3 (12%)

[0119] Thickness without compression - 0.31mm

[0120] Thickness after compression with 100kPa force - 0.17mm

[0121] Area density - 57g / m 2

[0122] The electrolyte absorption is 570 wt % based on the weight of the uncompressed separator.

[0123] The porosity before compression is 81%, and the porosity after compression with a force of 100 kPa is 44%.

[0124] Pore ​​diameter (measured by electron microscopy) ~150nm

[0125] Pressure drop - 1050Pa / 100g / m 2 .

[0126] A battery cell based on NMC / graphite chemistry with 0.5 mm electrode thickness (3D) was constructed using this separator. It showed excellent performance (up to 1000 A peak and 120 A continuous), high capacity utilization and relatively low losses.

[0127] Full charging from a discharged state can be achieved at a rate of C / 1.5 (1.5 hours), and even at such high-rate cycling, lithium dendrites did not penetrate the separator.

[0128] Figure 5 The graph in shows a smooth voltage curve at a current load of 120A - a charge and discharge time of approximately 1.5 hours.

[0129] Embodiment 4:

[0130] Inorganic soda-lime glass fibers, typically 0.5 to 5 mm in length and 20 to 1500 nm in thickness, are dispersed in water, the mixture is diluted and the acidity is adjusted to a pH of 3. The mixture is then poured onto a moving sieve, where it forms a uniform layer, which is dried at 150° C. to form a porous matrix. Titanium dioxide ceramic particles of a rutile crystal structure with an average particle size of 250 nm are introduced into the matrix by a wet method. The ceramic particles penetrate into the interior of the matrix. Unlike the previous embodiment, the titanium dioxide crystals do not have fibers that are mechanically adhered to the matrix, but they fill the entire volume of the matrix, thus making the porosity of the composite material 150 nm on average. The composite material is then dried at 350° C. to form a layer, from which separators are cut into the desired shape, and these separators are used in battery cells with three-dimensional electrodes of 0.5 mm thickness.

[0131] The separators show the following properties:

[0132] Composition: Glass (87%), TiO 2 (13%)

[0133] Thickness without compression - 0.32mm

[0134] Thickness after compression with 100kPa force - 0.18mm

[0135] Area density 60g / m 2

[0136] The electrolyte absorption is 600 wt % based on the weight of the uncompressed separator.

[0137] The porosity before compression is 79%, and the porosity after compression with a force of 100 kPa is 45%

[0138] Pore ​​diameter (measured by electron microscopy) ~150nm

[0139] Pressure drop - 1030Pa / 100g / m 2 .

[0140] A battery cell based on NMC / graphite chemistry with 0.5 mm electrode thickness (3D) was constructed using this separator. It showed stable discharge performance and low losses. The properties of this composite separator were similar to those of the glass-Al2O3 composite separator of Example 2. 2 O 3 Composite dividers are comparable. Figure 6 A cross-sectional detail of the separator is shown.

[0141] Embodiment 5:

[0142] Inorganic borosilicate glass fibers, typically 0.5 mm to 5 mm in length and 20 nm to 1500 nm in thickness, are dispersed in water, the mixture is continuously diluted with distilled water and the acidity is adjusted to a pH of 2.5. The mixture is then poured through a moving sieve, where a uniform layer is formed, and the layer is dried at 150° C. to form a porous matrix. Titanium dioxide ceramic nanoparticles of anatase crystal structure with an average particle size of 50 nm are introduced into the matrix by a wet method. The ceramic particles penetrate into the interior of the matrix and mainly fill the pores above the matrix to form a uniform shell layer, thereby changing the pore size of the composite material to an average value of 50 nm. The composite material is then dried at 350° C. to form a layer, from which separators are cut into the desired shape, and these separators are used in batteries with three-dimensional electrodes with a thickness of 0.5 mm.

[0143] The separators show the following properties:

[0144] Composition: Glass (90%), TiO 2 (10%)

[0145] Thickness without compression - 0.44mm

[0146] Thickness after compression with 100kPa force - 0.17mm

[0147] Area density - 55g / m 2

[0148] The electrolyte absorption was 590 wt % based on the weight of the matrix before compression.

[0149] The porosity before compression is 57%, and the porosity after compression with a force of 100 kPa is 22%

[0150] Pore ​​diameter (measured by electron microscopy) ~50nm

[0151] Pressure drop -1270Pa / 100g / m 2 .

[0152] Figure 7 The oriented matrix nanofiber structure with a thickness of 446 nm is shown to be filled with TiO 2 Nanoparticles, the TiO 2A cross section of a separator with nanoparticles infiltrated to a depth of about 200 microns, forming a shell with a pore size of about 25 nm. Separators of this thickness and such small pore sizes are difficult to produce with traditional polymer layers. The ability to form separators with any pore size allows for the properties of fast-charging separators to be effectively altered.

[0153] Figure 8 Electron microscope image showing the surface of a composite separator with anatase nanoparticles, with particle and pore sizes less than 50 nm.

[0154] Cells constructed using this separator with 0.5 mm electrode thickness (3D) and NMC / graphite chemistry show clean charge and discharge patterns even at relatively fast C / 2 cycling rates ( Fig. 9 ).

[0155] Full charging from a discharged state can be achieved at a rate of C / 2 (2 hours) without lithium dendrites crossing the separator.

[0156] Embodiment 6:

[0157] Inorganic glass fibers, typically 0.5 mm to 5 mm in length and 20 nm to 1000 nm in thickness, are dispersed in water, the mixture is diluted and the acidity is adjusted to a pH of 2.5. The mixture is then poured through a moving sieve, where a uniform layer is formed, which is dried at 150°C to form a porous matrix. Short glass fibers, typically 5 μm to 10 μm in length, are introduced into the matrix by a wet process. The short fibers penetrate into the interior of the matrix and are mechanically connected to the fibers of the matrix. The composite is then dried at 350°C to form a layer from which separators are cut. These separators are used in batteries with 0.5 mm thick three-dimensional electrodes.

[0158] The separators show the following properties:

[0159] Composition: Glass 100%

[0160] Area density - 55g / m 2

[0161] Thickness without compression - 0.33mm

[0162] Thickness after compression with 100kPa force - 0.17mm

[0163] The electrolyte absorption was 610 wt % based on the weight of the matrix before compression.

[0164] The porosity before compression is 76%, and the porosity after compression with a force of 100 kPa is 39%

[0165] Pore ​​size (determined by electron microscopy) <300nm

[0166] Pressure drop - 1050Pa / 100g / m 2 .

[0167] A battery cell based on NMC / graphite chemistry with 1 mm electrode thickness (3D) built using this separator showed stable performance, low losses, and full capacity utilization (comparable to the separator of Example 2). Fig.10 The stable voltage process of the cycle can be clearly seen.

[0168] Embodiment 7 (comparative example):

[0169] Commercially available cellophane commonly used in high-end lead-acid batteries was used as separators. These separators were used / tested in cells with 0.5 mm thick NMC / graphite 3D electrodes.

[0170] The separators show the following properties:

[0171] Composition: Glass 93%, PVA 7%

[0172] Thickness without compression - 0.3mm

[0173] Area density - 60g / m 2 .

[0174] A battery cell based on NMC / graphite chemistry with 0.5 mm electrode thickness (3D) built using this separator has almost unusable properties. Even in the case of extremely slow charging for 36 hours, the separator fails already at 3.9 V, followed by overcharging, a sharp rise in battery temperature, voltage stagnation, and the risk of battery failure and explosion. The course of voltage, current and temperature is as follows Fig.11 shown.

[0175] Embodiment 8 (comparative example):

[0176] A commercial 23 μm plastic separator was used in an otherwise identical battery cell based on NMC / graphite chemistry with 0.5 mm electrode thickness (3D). The advantages of the inorganic separator are evident from the rapid degradation and significantly higher losses compared to the composite separator according to the invention. In the inorganic separator, the specific resistance does not increase during cycling and there is no risk of lithium dendrites growing through the separator.

[0177] Fig.12 The current, voltage and temperature curves for the first 300 cycles are shown. The rapid drop in capacity is evident from the reduction in cycle time. As the internal resistance increases, the losses during cycling also increase.

[0178] Industrial Applicability

[0179] The separator according to the present invention can be used for producing lithium batteries.

Claims

1. A separator for a lithium battery having an electrode having a thickness greater than 0.1 mm, characterized in that The separator is formed by interwoven non-conductive inorganic fibers, optionally together with an additive of non-conductive inorganic particles; wherein the length of the fibers is in the range of 0.5 mm to 30 mm, and the thickness of the fibers is in the range of 20 nm to 1500 nm; wherein the material of the fibers is glass; the pore size of the separator is in the range of 0.02 microns to 2.5 microns, wherein the pore size of the separator is the average pore size of the separator determined by averaging at least 50 pore diameter values ​​read from an electron microscope image; the absorbance of the separator, expressed as the weight of an electrolyte 1M LiPF6 immersed in ethylene carbonate / dimethyl carbonate with a volume ratio (v:v) = 1:1, is 1 to 10 times the weight of the separator.

2. The separator according to claim 1, characterized in that The porosity of the separator measured for the separator without compression is in the range of 50% to 90% and / or the porosity of the separator measured after compressing the separator with a force of 100 kPa is in the range of 20% to 55%.

3. The separator according to claim 1 or 2, characterized in that: At least 90% by weight of the fibers have a thickness in the range of 20 nm to 500 nm.

4. The separator according to any one of claims 1 to 3, characterized in that The pore size of the separator is in the range of 20 nm to 1000 nm, more preferably in the range of 20 nm to 500 nm, even more preferably in the range of 20 nm to 150 nm.

5. The separator according to any one of claims 1 to 4, characterized in that: The separator contains an admixture of non-conductive inorganic particles, wherein the weight ratio of the particles to the total weight of the separator is at most 20 wt %, and the non-conductive inorganic particles are particles having a maximum dimension in the range of 10 nm to 700 nm, preferably at most 500 nm, more preferably at most 200 nm to 300 nm, or the non-conductive inorganic particles are glass fibers having a length of at most 20 microns, preferably at most 10 microns and a thickness in the range of 20 nm to 1500 nm.

6. The separator according to claim 5, characterized in that The non-conductive inorganic particles are made of ceramic material and / or glass, the ceramic material is selected from the group consisting of silicon oxide, aluminum oxide, or zirconium oxide, titanium oxide, silicate, titanate, aluminosilicate, zirconium silicate, basalt, and mixtures thereof, and the glass is selected from groups A, C, D, E, R based on aluminoborosilicate or aluminosilicate with alkaline oxides such as CaO, MgO or B2O3.

7. The separator according to any one of claims 1 to 6, characterized in that After being compressed with a force of 100 kPa, the thickness of the separator is in the range of 0.050 mm to 2 mm.

8. The separator according to any one of claims 1 to 7, characterized in that At a layer thickness of 100 μm, the area density of the separator layer is 10 g / m 2 Up to 200g / m 2 within the range.

9. The separator according to any one of claims 1 to 8, characterized in that The matrix of the separator is also filled with particles that prevent polysulfide migration, preferably selected from the group consisting of titanium dioxide, titanium nitride, graphene, zirconium oxide.

10. A lithium battery, characterized in that: The lithium battery contains at least one pair of electrodes separated by a separator according to any one of the preceding claims, wherein the ratio of the thickness of the separator layer to the thickness of the electrode is in the range of 1:2 to 1:10, and the electrode preferably has a thickness of 100 microns to 4 mm, more preferably 0.3 mm to 2 mm, and most preferably 0.5 mm to 1 mm.

Citation Information

Patent Citations

  • Separator for high energy rechargeable lithium battery

    EP1146576A1

  • Inorganic separator-electrode-unit for lithium-ion batteries, method for the production thereof and use thereof in lithium batteries

    EP1803177A2

  • Lithium accumulator and the method of producing thereof

    EP2371019A1

  • Lithium accumulator

    EP2727171A1

  • Lithium accumulator and the method of producing thereof

    US10581083B2